1998
DOI: 10.1097/00004647-199805000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Ischemia after Bilateral Carotid Artery Occlusion and Intraluminal Suture Occlusion in Mice: Evaluation of the Patency of the Posterior Communicating Artery

Abstract: Summary: Cerebral ischemia models using mice have drawn increasing attention, particularly because of the availability of transgenic animals, However, the variability of intracranial vas culature at the circle of Willis in mice can influence the degree of ischemia in both the bilateral common carotid artery (CCA) occlusion and intraluminal suture occlusion models, We have developed a method to predict the extent of the anastomosis between carotid and vertebrobasilar circulation in three mouse strains (C57BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
206
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(219 citation statements)
references
References 23 publications
12
206
0
1
Order By: Relevance
“…Since this method yields highly reproducible and consistent CA1 neuronal injury, as compared with other models (Kitagawa et al, 1998;Wellons et al, 2000), comparison of ischemic outcomes in wild-type and p53-deficient mice could show a link between p53 and ischemic neuronal injury in vivo.…”
Section: Introductionmentioning
confidence: 92%
“…Since this method yields highly reproducible and consistent CA1 neuronal injury, as compared with other models (Kitagawa et al, 1998;Wellons et al, 2000), comparison of ischemic outcomes in wild-type and p53-deficient mice could show a link between p53 and ischemic neuronal injury in vivo.…”
Section: Introductionmentioning
confidence: 92%
“…This appears to be the case in the study of Tabrizi et al 34 Interstrain differences in intracranial vascular anatomy affecting the circle of Willis are another factor influencing the degree of ischemia. [45][46][47][48] As the methods of molecular biology and genetics continue to be applied with increasing success to the study of ischemic brain injury, one expects not only an increasingly sophisticated understanding of pathophysiology but also major advances in the rational design and implementation of neuroprotective strategies that will be tested in the clinic and succeed, eventually, in diminishing death and disability in patients with ischemic stroke. …”
Section: See Page 2801mentioning
confidence: 99%
“…It is now apparent that the sensitivities to ischemic insult between different mouse strains is a problematic issue (Sheldon et al, 1998;Wellons et al, 2000) that necessitates optimizing ischemic duration for each mouse strain. In addition, we and others have noted variability stemming from individual differences in collateral flow through the circle of Willis, even within one strain (Fujii et al, 1997;Kitagawa et al, 1998;Sheng et al, 1999;Beckmann, 2000;Wellons et al, 2000). Therefore, knowing the patency of PcomA of an individual mouse before conducting surgery would be ideal for optimizing this model.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, knowing the patency of PcomA of an individual mouse before conducting surgery would be ideal for optimizing this model. Some investigators have suggested that residual cerebral blood flow (rCBF) after the initiation of ischemia could be used as a predictor of the presence of PcomA (Kitagawa et al, 1998;Yonekura et al, 2004). It was also reported that mice undergoing transient global ischemia by 3-vessel occlusion in which the effect of collateral blood flow had been eliminated by successful basilar artery occlusion would have a rCBF <10% of baseline at 2.5 min after ischemia was initiated (Yonekura et al, 2004).…”
Section: Introductionmentioning
confidence: 99%